Current Perspectives in Human T-Cell Leukemia Virus Type 1 Infection and Its Associated Diseases - Miura, Michi; Naito, Tadasuke; Saito, Mineki (Frontiers in Medicine, 2022)
Human T-cell leukemia virus type 1 (HTLV-1) is a replication-competent human retrovirus associated with two distinct types of diseases: a malignancy of mature CD4+ T cells called adult T-cell leukemia-lymphoma (ATL) and a chronic inflammatory central nervous system disease HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). It was the first human retrovirus ever associated with a human cancer. Although most HTLV-1-infected individuals remain asymptomatic for life, a subpopulation develops ATL or HAM/TSP. Although the factors that cause these different manifestations of HTLV-1 infection are not fully understood, accumulating evidence suggests that the complex virus-host interactions, as well as the host immune response against HTLV-1 infection, appear to regulate the development of HTLV-1-associated diseases. This review outlines and discusses the current understanding, ongoing developments, and future perspectives of HTLV-1 research.